Philosophical Baseline of the Religious Pilgrimage and Its Significance for Dialogue among Religions - Hamsah, Ustadi; Zarbaliyev, Habib; Soehadha, Moh (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
As a religious phenomenon, pilgrimages have varying orientations. The diversity of orientations is determined by the level of motivation and meaning of the symbols attached to the pilgrimage. The connection between exposure and awareness of pilgrimage becomes the basis for pilgrims to interpret deeper aspects. The problem that arises later is the axiological interpretation of pilgrimage. In this reflective and theoretical study, the data was collected through in-depth reading about the pilgrimage of currently available academic literature. By applying philosophical analysis, the following article seeks to trace the most profound meaning of pilgrimage for creating positive interfaith relations. This study concludes that the most profound aspect of pilgrimage consciousness is archetypes that explain the uniformity of the spirit of pilgrimage carried out by the people of the religions. With that archetype, interfaith relations are easy to build because of the awareness of humanity and the apparent solidarity among religious adherents